Hak Konstitusional Bagi Penyandang Disabilitas Perspektif Siyāsah - Wibowo, Irham; Rahmah, Nur (Jurnal EL-QANUNIY: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2024)
The purpose of law is closely related to natural rights, because humans as legal subjects have the right to freedom, the right to life, and the right to property. These rights originate from human nature which is independent of all forms of legal systematics and constitutional practices. The logical consequence that needs to be understood is that the government must be able to provide guarantees to all its citizens, not oppress or exploit them. Automatically, every citizen has the same rights and opportunities in various fields. One of the rights for citizens guaranteed by the constitution is political rights. Of the hundreds of millions of Indonesian citizens there is a group called people with disabilities. Their existence is accommodated through Law Number 8 of 2016 concerning Persons with Disabilities. In Article 13 letter (a) of Law Number 8 of 2016 concerning Persons with Disabilities, it is stated that they have political rights, namely to vote and be elected to public office. These statutory regulations open up the same opportunities as people in general and at the same time confirm that the constitutional mandate in Article 27 paragraph (1) of the 1945 Constitution of the Republic of Indonesia has been carried out. So the logical consequence is that public office is no longer a privilege for elite groups, so that people with disabilities can elect and be elected as executive officials, members of the legislature or judiciary, as well as positions in other institutions or bodies. People with disabilities are not miserable people whose existence is underestimated. In the siyāsah perspective, they are the same as other humans. Islam never discredits certain groups, but Islam mainstreams justice and generalizes services for its people, including people with disabilities. This article underlines the need for active involvement of people with disabilities in Indonesia in political activities. In fact, they also have the same opportunities and opportunities as people in general to fulfill all kinds of constitutional rights, such as voting and being elected in general elections. Meanwhile, the context of Siyasah Syar'iyyah is strengthened through His words in Surah al-Maidah verse 8 that the command to do justice to humans includes fulfilling all the rights of people with disabilities among us.